2011
DOI: 10.1016/j.juro.2011.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Delay of Surgery in Men With Low Risk Prostate Cancer

Abstract: In men who met the D'Amico low risk criteria, a surgical delay of 6 months or more was associated with significantly worse radical prostatectomy outcomes, including more pathology upgrading and a higher rate of biochemical progression. Low risk patients choosing to defer initial definitive therapy should be counseled regarding the possibility of worse treatment outcomes at a later date.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
48
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 15 publications
6
48
0
Order By: Relevance
“…11,[26][27][28][29] Understandably, this is one of a few ways to ethically study SWT with prolonged delays. Otherwise, in most other global centres, men who are not eligible for AS are operated with minimal delay, considering greater access to surgical resources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,[26][27][28][29] Understandably, this is one of a few ways to ethically study SWT with prolonged delays. Otherwise, in most other global centres, men who are not eligible for AS are operated with minimal delay, considering greater access to surgical resources.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, very few studies have reported a trend toward increased risk of biochemical recurrence (BCR)-associated with surgical delays for prostate cancer. [9][10][11] Therefore, the true impact of surgical delay remains controversial and the acceptable wait time is currently unknown. As such, we sought to address the impact of SWT to RARP on pathological outcomes for patients in two major academic centres in Canada.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an analysis of 17,943 patients with low-risk prostate cancer (i.e., candidates for active surveillance) treated with radical prostatectomy (RP) in the US between 2010–2011 showed that upgrading, upstaging, or nodal metastases occurred in 45% of men and that the deferral of radical prostatectomy for more than 12 months was associated with an 1.7-fold increased risk of non-organ confined disease after surgery (4). Additionally, in men with low risk prostate cancer, the deferral of radical prostatectomy is associated with significantly worse radical prostatectomy outcomes, including more pathology upgrading and a higher rate of biochemical progression (5). Therefore, additional tools beyond clinical staging are needed to improve risk stratification and optimize effective use of active surveillance (3).…”
Section: Introductionmentioning
confidence: 99%
“…In practice, the 10-year disease-specific survival of men who select AS is between 97% and 100%, 19,20 but although small, there is always the risk of missing the curative window. Recent analyses reveal that men who defer treatment have higher incidences of biochemical progression following definitive treatment, 21 with up to 50% treatment failure in a large cohort of patients. 19 This could be a reason for poor acceptance and adherence to AS by patients and physicians.…”
Section: Ftmentioning
confidence: 99%